P173 PK PD rationale and efficacy of isavuconazole treatment after failure of amphotericin B and posaconazole for COVID-19 associated cranial Mucormycosis. (20th September 2022) - Soman, Rajeev; Chakraborty, Sourabh; Joe, Geethu; Purandare, Bharat; Joshi, Rasika; Patwardhan, Sampada
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Objective: This case series describes our experience of using isavuconazole (ISVCZ), along with TDM, after the failure of treatment with Amphotericin B (AmB) and Posaconazole (PCZ) due to the better PK PD properties of ISVCZ. Patients and methods: There were 6 patients with ROCM who had disease progression despite surgical debridement and adequate treatment with AmB and PCZ. Anti-fungal treatment was switched to ISVCZ which achieves levels in brain (1.86x)R and in bone-marrow (3x)R as compared to serum levelsR. Results: PK PD considerations for ISVCZ treatment considering the likely levels in brain and bone-marrow and the MIC of majority of Mucoralean molds as ≤4R Table 1 Table 2 Results of treatment Conclusion: Treatment with ISVCZ may mitigate some of the challenges in ROCM due to its PK PD properties. TDM for ISVCZ is not routinely recommended, but could be used to ensure high plasma exposures and enhanced penetration to the site of infection. Our results are encouraging although there are several limitations of a case series, confounding variables involved, and the use of ISVCZ as salvage after failure of previous treatment. Clinical success in this series suggests that extrapolative PK PD considerations in using ISVCZ for such 'difficult to treat' patients may be justified.